Cytosolic Internalization of Anti-DNA Antibodies by Human Monocytes Induces Production of Pro-inflammatory Cytokines Independently of the Tripartite Motif-Containing 21 (TRIM21)-Mediated Pathway - Park, Hyunjoon; Kim, Minjae; Seo, Youngsil; Ham, Yeonkyoung; Cho, Mi-Young; Kwon, Myung-Hee (Frontiers in Immunology, 2018)
Anti-DNA autoantibodies are a hallmark of systemic lupus erythematosus (SLE). A subset of anti-DNA IgG autoantibodies is cell-internalizable; thus they can enter living cells in the form of free IgG. However, the contribution made by the Fc region of internalized free-form IgG to the cytokine response has not been studied, despite the recent discovery of tripartite motif-containing 21 (TRIM21), a cytosolic Fc receptor involved in immune signaling. This study used an internalizable IgG anti-DNA antibody (3D8) to examine the cytokine responses of human monocytes to the Fc region of cytosolic free IgG. Internalization of 3D8 IgG and a 3D8 single-chain variable fragment-Fc (scFv-Fc) induced production of IL-8 and TNF-α via activation of NF-κB. By contrast, a 3D8 scFv (comprising variable domains alone) did not. This suggests Fc-dependent cytokine signaling. A 3D8 IgG-N434D mutant that is not recognized by TRIM21 induced greater production of cytokines than 3D8 IgG. Moreover the amounts of cytokines induced by 3D8 IgG in TRIM21-knockdown THP-1 cells were higher than those in control cells, indicating that cytokine signaling is not mediated by TRIM21. The results suggest the existence of a novel Fc-dependent signaling pathway that is activated upon internalization of IgG antibodies by human monocytes.